2022
DOI: 10.1021/acsami.1c23994
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Electrolyte Dielectrics Enable Efficient Exciton-Polaron Quenching in Organic Semiconductors for Photostable Organic Transistors

Abstract: The photoelectric response of organic field-effect transistors (OFETs) will cause severe photoelectric interference, which hinders the applications of OFETs in the light environment. It is highly challenging to relieve this problem because of the high photosensitivity of most organic semiconductors. Here, we propose an efficient "exciton-polaron quenching" strategy to suppress the photoelectric response and thus construct highly photostable OFETs by utilizing a polymer electrolyte dielectricpoly(acrylic acid)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…It is worth pointing out that the EPSC are hardly affected by the same UV-light stimulation (Figure 1j) without the presence of AlO X nanoparticles, and there is even a negative photoconductance effect, which is mainly due to the inhibition of the light response by the ion movement. [56] Unlike Figure 1d,k shows the similar A 1 and A 10 during three photostimulation cycles without AlO X , which is consistent with the above results and further indicates that AlO X is beneficial for carrier separation and improving optical response. Additionally, as fabricated flexible intelligent optical synaptic devices can maintain stable EPSC current even under bending radius at 2.5 mm (Figure S4a, S4b, Supporting Information), demonstrating outstanding flexibility.…”
Section: Improved Multiwavelength Optical Response Devicessupporting
confidence: 87%
See 1 more Smart Citation
“…It is worth pointing out that the EPSC are hardly affected by the same UV-light stimulation (Figure 1j) without the presence of AlO X nanoparticles, and there is even a negative photoconductance effect, which is mainly due to the inhibition of the light response by the ion movement. [56] Unlike Figure 1d,k shows the similar A 1 and A 10 during three photostimulation cycles without AlO X , which is consistent with the above results and further indicates that AlO X is beneficial for carrier separation and improving optical response. Additionally, as fabricated flexible intelligent optical synaptic devices can maintain stable EPSC current even under bending radius at 2.5 mm (Figure S4a, S4b, Supporting Information), demonstrating outstanding flexibility.…”
Section: Improved Multiwavelength Optical Response Devicessupporting
confidence: 87%
“…[54,55] The light absorption, exciton separation are inhibited and exciton quenching presented when there is only PVDF-HFP, which together results in rapidly declining current. [56,57] By incorporating 5 nm AlO X , the exciton separation process is accelerated, and a detailed mechanism is discussed in Section 2.5. To further demonstrate the universality of this phenomenon, the same structure was constructed on the silicon substrate (Figure S1, Supporting Information), demonstrating that the introduction of AlO X further increased the hysteresis and optical synaptic response characteristics.…”
Section: Improved Multiwavelength Optical Response Devicesmentioning
confidence: 99%
“…Excitons generated in the emissive layer can undergo energy transfer or charge transfer to charge carriers (polaritons) in the highly doped PEDOT:PSS, or other polyelectrolytes, leading to exciton quenching. [ 30,31 ] Furthermore, EL in these devices is generated by electron–hole recombination near the SY/HIL interface; therefore, interface quenching effects observed in photoluminescence experiments with 40 nm thick SY films may underestimate the extent to which in EL is quenched, which may be why the EQE of PEDOT:PSS devices is relatively lower than that would be expected based on the relative PL quenching alone. [ 32 ] Li:PSS S exhibited slightly reduced PL intensity upon increasing the PEDOT:PSS ratio.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the photo-generated excitons can be quenched by polarons. 49,[55][56][57][58][59] Moreover, the reorganization energies of PQ-4FP and PQ-4ClP are 364.45 eV and 188.92 eV, respectively (Fig. S12, ESI †).…”
Section: Resultsmentioning
confidence: 99%